2006
DOI: 10.1007/s10856-006-9223-9
|View full text |Cite
|
Sign up to set email alerts
|

Study of biodegradable and self-expandable PLLA helical biliary stent in vivo and in vitro

Abstract: Biodegradable stents have advantages for the treatment of benign and malignant biliary stricture, especially eliminating the need for stent removal. In our present work, helical poly-l-lactic acids (PLLA) stent was fabricated and evaluated in vivo and in vitro. For in vivo study, bile duct injury canine models were made by transection of common bile ducts. Duct to duct anastomosis was done with helical PLLA biodegradable stents. Scanning electron microscopy (SEM) and histopathology were performed after three m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(37 citation statements)
references
References 6 publications
0
36
0
1
Order By: Relevance
“…However, the use of covered metal stents needs further evaluation to determine their therapeutic effectiveness. Self-expanding stents made of bioabsorbable material may offer several advantages compared to the plastic and self-expanding metal stents 85,86. Studies in porcine models show that these stents offer improved patency because of their large diameter, lower biofilm accumulation and reduced incidence of bile duct proliferative changes.…”
Section: Future Directionsmentioning
confidence: 99%
“…However, the use of covered metal stents needs further evaluation to determine their therapeutic effectiveness. Self-expanding stents made of bioabsorbable material may offer several advantages compared to the plastic and self-expanding metal stents 85,86. Studies in porcine models show that these stents offer improved patency because of their large diameter, lower biofilm accumulation and reduced incidence of bile duct proliferative changes.…”
Section: Future Directionsmentioning
confidence: 99%
“…These stents are still in the developmental stage and have yet to progress to in vivo studies. It is important to note, that while the focus of this section has been on application of stents in coronary arteries, BSMP stents are also being developed for use in other locations in the body including the urethra, trachea, bile ducts, and intracranial arteries . Application to other areas requires changing the specific stent design, dimensions, and delivery method.…”
Section: Medical Applicationsmentioning
confidence: 99%
“…In addition, by comparison with common slotted and wire mesh stents, which have sharp edges, helical stents may reduce potential injury sites upon insertion and subsequently reduce the incidence of restenosis [Bedoya, 2006;Gervaso, 2008]. Beyond some clinical reports [Vaajanen, 2003;Tamura, 1996;Vogt, 2004;Meng, 2006;Venkatraman, 2003], very few studies have been undertaken to evaluate mechanical performance and design of helical stents. It has been found that a typical PLLA-based helical stent has a collapse pressure of 2.5 bar.…”
Section: Helical Stentsmentioning
confidence: 99%